Sheng Mai San protects H9C2 cells against hyperglycemia-induced apoptosis - Bing Pang; Li-Wei Shi; Li-juan Du; Yun-Chu Li; Mei-Zhen Zhang; Qing Ni (BMC, 2019)
Abstract Background Sheng Mai San (SMS) has been proven to exhibit cardio-protective effects. This study aimed to explore the molecular mechanisms of SMS on hyperglycaemia (HG)-induced apoptosis in H9C2 cells. Methods HG-induced H9C2 cells were established as the experimental model, and then treated with SMS at 25, 50, and 100 μg/mL. H9C2 cell viability and apoptosis were quantified using MTT and Annexin V-FITC assays, respectively. Furthermore, Bcl-2/Bax signalling pathway protein expression and Fas and FasL gene expression levels were quantified using western blotting and RT-PCR, respectively. Results SMS treatments at 25, 50, 100 μg/mL significantly improved H9C2 cell viability and inhibited H9C2 cell apoptosis (p < 0.05). Compared to the HG group, SMS treatment at 25, 50, and 100 μg/mL significantly downregulated p53 and Bax expression and upregulated Bcl-2 expression (p < 0.05). Moreover, SMS treatment at 100 μg/mL significantly downregulated Fas and FasL expression level (p < 0.05) when compared to the HG group. Conclusion SMS protects H9C2 cells from HG-induced apoptosis probably by downregulating p53 expression and upregulating the Bcl-2/Bax ratio. It may also be associated with the inhibition of the Fas/FasL signalling pathway.